High-Resolution Modeling of Mesoscale Circulation in the Atmospheric Boundary Layer over a Complex Coastal Area - Hee-Jeong Lim; Young-Hee Lee (Atmosphere, 2021)
We evaluated the performance of the high-resolution (333 m) Weather Research and Forecasting (WRF) model in simulating the flow structure at a complex coastal site in Boseong, South Korea, on 15 July 2018, against observations obtained from a 300 m tower and radiosonde, and analyzed the model results to interpret the measurements. The study site is surrounded by mountains, valleys, and bays, and is adjacent to the South Sea; thus, it is influenced by terrain-forced flow and thermally driven circulation. The study day was characterized by the development of nighttime low-level wind maximum (LLWM) and daytime sea breeze under weak synoptic wind conditions. Although the WRF model simulated the onset and cessation of a sea breeze later than was observed, it showed good skill in reproducing the near-surface temperatures, wind vectors, and vertical profiles of potential temperatures and wind vectors in the atmospheric boundary layer at the study site. We analyzed the model results at 05:30 and 14:30 LST when the model’s performance was good for wind. At 05:30 LST, hydraulic jump produced weak wind conditions below 300 m above ground level (AGL), and westerly down-valley flow developed near the surface, leading to an LLWM. At 14:30 LST, heating over land produced a thermal high over land at 1800 m AGL, counteracting the synoptic pressure gradient, and leading to weak wind conditions at this level. We performed three sensitivity simulations to examine the dependence of flow structure on the horizontal and vertical resolution. The results show that an early-morning hydraulic jump can be simulated by applying a high-resolution model in both the horizontal and vertical grids, and the simulated onset and cessation times of the sea breeze depend on the model’s resolution. The dependence of flow structure on the model resolution has been discussed.